Silver-palladium-nickel-copper graphene composite relay electrical contact and preparation method thereof

By using silver nickel -copper graphene composite material to make relay electrical contacts, the contact adhesion and vulcanization problem of contacts in existing technologies have been solved, and more stable contact resistance and lower contact temperature rise are achieved.

CN119381188APending Publication Date: 2025-01-28SHENYANG RAILWAY SIGNAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411601498.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing relay electrical contacts are prone to contact adhesion and vulcanization problems during long-term use, resulting in unstable contact resistance and poor thermal conductivity.

Method used

Electrical contacts are made of silver nickel -copper graphene composite materials. The mixing and ball mills of nano -silver in the ethanol solution can improve the moist and distribution of the material. Sulfurization and weldability.

Benefits of technology

Improve the anti -vulcanization of the electrical contact and the stability of the contact resistance, reduce the temperature rise, and enhance the wear resistance and welding of the contact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381188A_ABST
    Figure CN119381188A_ABST
Patent Text Reader

Abstract

The invention discloses a silver-palladium-nickel-copper graphene composite relay electrical contact and a preparation method thereof, and relates to the technical field of relay contact preparation, and the silver-palladium-nickel-copper graphene composite relay electrical contact comprises the following components in percentage by mass: 35%-45% of graphene powder, 40%-50% of nano silver powder, 4%-5% of nickel powder, 5%-6% of nano palladium powder and 5%-6% of nano copper powder. The defects of an original silver graphite contact are overcome, the vulcanization resistance of the electric contact is enhanced, and meanwhile the stability of the contact resistance of the electric contact is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of relay contact preparation, and in particular to a silver-palladium-nickel-copper-graphene composite relay electrical contact and a preparation method thereof. Background Art

[0002] Common relay electrical contacts on the market are generally made of copper-silver alloy, silver cadmium oxide, silver tin oxide and silver nickel. Contact adhesion often occurs in the above-mentioned contact materials under long-term electrical life conditions. The essence of the contact adhesion problem is that the contact has poor resistance to fusion welding. In order to solve the problem of contact adhesion, silver-graphite contacts, also called silver-carbon contacts, appear in the prior art. Although silver-graphite contacts have strong resistance to fusion welding, they also have some disadvantages. The first disadvantage is that due to the poor wettability of silver and graphite, the bonding between silver and graphite molecules is poor; the second is that the resistivity of graphite is greater than that of silver. At the same time, the processing technology of various manufacturers varies greatly, and there is an uneven distribution of graphite in silver, so the contact resistance of the silver-graphite contact is unstable; the third is that due to the high proportion of silver in the silver-graphite contact, the silver on the surface of the silver-graphite contact is prone to sulfidation in an environment with a high sulfur content, and is corroded to form a silver sulfide film, which also increases the resistance of the silver-graphite contact; the fourth is that the thermal conductivity of graphite is general, which increases the temperature rise of the contact between the silver-graphite contacts, which is not conducive to heat conduction; the fifth is that the silver-graphite contact itself has poor weldability with the phosphor copper sheet and the magnesium copper sheet. Summary of the invention

[0003] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a silver-palladium-nickel-copper graphene composite relay electrical contact and a preparation method thereof, which overcomes the shortcomings of the original silver-graphite contact, enhances the anti-sulfurization property of the electrical contact, and improves the stability of the contact resistance of the electrical contact.

[0004] In order to achieve the above object, the main technical solutions adopted by the present invention include: A silver-palladium-nickel-copper-graphene composite relay electrical contact, comprising the following components by mass percentage: 35%-45% graphene powder, 40%-50% nano silver powder, 4%-5% nickel powder, 5%-6% nano palladium powder and 5%-6% nano copper powder.

[0005] Furthermore, the graphene powder has a particle size of 10 nm, the nano silver powder has a particle size of 40 nm to 50 nm, the nickel powder has a particle size of 3 μm to 5 μm, the nano palladium powder has a particle size of 20 nm to 50 nm, and the nano copper powder has a particle size of 10 nm to 30 nm.

[0006] A method for preparing the silver-palladium-nickel-copper-graphene composite relay electrical contact comprises the following steps: Step S01, mixing graphene powder, an organic solvent and deionized water to prepare a graphene solution; Step S02, adding 80%-90% of the total amount of nano silver powder into the graphene solution, and stirring to obtain a silver graphene solution; Step S03, sealing the silver-graphene solution obtained in step S02, leaving it to stand, filtering it, drying the filtrate, and stirring it in a ball mill to obtain a silver-graphene composite powder; Step S04, adding the remaining 10%-20% of nano silver powder, nickel powder, nano palladium powder, and nano copper powder into ethanol and deionized water, stirring, oscillating, filtering, obtaining a mixed solution filtrate, and drying the filtrate to obtain a silver-nickel-palladium-copper mixed powder; Step S05, after the silver-graphene composite powder and the silver-nickel-palladium-copper mixed powder are stirred, the mixture is sealed and allowed to stand, hot isostatic pressing is performed on the mixed material after the standing, and sintering is performed in a cavity containing hydrogen to form a material block; the material block is molded or wire-cut according to the required contact shape to obtain a molded contact; Step S06: Decarburize the welding layer of the formed contact with a solvent, spray silver on the decarburized silver layer, and then weld it to the contact piece.

[0007] Furthermore, in the step S01, the graphene powder is added to ethanol and deionized water, and stirred at a constant speed for 4 h to 5 h using a stirrer. The stirred solution is placed in an ultrasonic cleaning pot and vibrated for 30 min to obtain a graphene solution.

[0008] Furthermore, in the step S02, the silver graphene solution is added to the graphene solution and placed in a mixer for thorough stirring for 2 h to 4 h to obtain a silver graphene solution.

[0009] Furthermore, in step S03, the silver-graphene solution is sealed and allowed to stand for 3 h to 4 h, then filtered five times with 300-mesh filter paper, the filtrate is dried in a drying oven at 90° C. for 12 h to 14 h, and the dried silver-graphite composite powder is placed in a ball mill and fully stirred.

[0010] Furthermore, in the step S04, the nano silver powder, nickel powder, nano palladium powder and nano copper powder are added to ethanol and deionized water and stirred in a stirrer for 2 h to 4 h, and then oscillated in an ultrasonic cleaning pot for 1 h to 2 h. The oscillated solution is filtered five times with 300 mesh filter paper, and the filtered mixed solution is placed in a drying oven at 90° C. and dried for 12 h to 14 h.

[0011] Furthermore, in the step S05, the silver-graphene composite powder and the silver-nickel-palladium-copper mixed powder are placed in a ball mill and stirred for 5h~6h, the ball milling speed is 5~10 times / second, and the mixture is sealed and allowed to stand for 3h~4h. The mixed material after standing is placed in an isostatic pressing device for hot isostatic pressing at a pressure of 200MPa~300MPa and maintained for 15min~20min; and sintered in a cavity containing hydrogen at a sintering temperature of 950℃~1050℃.

[0012] Furthermore, in step S06, the decarbonization solvent is composed of 25% to 30% decarbonization powder, 60% to 65% ethanol, and 10% to 15% sulfolane.

[0013] Furthermore, in the step S06, the silver is sprayed by a magnetron sputtering process, the silver spraying rate is 0.623 nm / s, the sputtering power is 30 W, the working gas pressure is 3.5 Pa, and the silver spraying thickness is 50 μm to 80 μm.

[0014] The beneficial effects of the present invention are as follows: the present invention forms a solution of graphene and nano-silver through ethanol, improves the wettability between the molecules, allows them to fully contact and fuse, and the combination of graphene and nano-silver is more complete than the combination of graphite and nano-silver, and the distribution is more uniform. At the same time, graphene has lower resistivity, higher thermal conductivity and electrical conductivity than graphite, reduces contact resistance, reduces the temperature rise of the contact points between the contacts, and the addition of nano-silver powder, nickel powder, nano-palladium powder and nano-copper powder is to improve the anti-sulfurization property of silver and improve the stability of the contact resistance of the contact. The decarburization of the silver-graphene contact welding layer and the magnetron sputtering silver spraying are to better allow the contact to be welded to the copper sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a photograph of the welding layer of the silver alloy graphene composite contact after decarburization prepared by the present invention; Figure 2 This is a photograph of the welding layer of the silver alloy graphene composite contact without decarburization prepared by the present invention; Figure 3 This is a side view photo of the soldering of the silver-graphene composite contact and the phosphor copper sheet after decarburization of the welding layer; Figure 4 This is a main view photo of the soldering of the silver-graphene composite contact and the phosphor copper sheet after decarburization of the welding layer; Figure 5 The side view photo shows that the silver-graphene composite contact and the phosphor copper sheet cannot be soldered because there is no decarburization in the welding layer; Figure 6 The main view photo shows that the silver-graphene composite contact and the phosphor copper sheet cannot be soldered because there is no decarburization in the welding layer; Figure 7 This is a diagram showing the change in contact arcing energy obtained in Example 1; Figure 8 This is a diagram showing the change in contact arcing energy obtained in comparative example 1. DETAILED DESCRIPTION

[0016] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0017] The present invention provides a silver-palladium-nickel-copper-graphene composite relay electric contact and a preparation method thereof, wherein the silver-palladium-nickel-copper-graphene composite relay electric contact comprises the following components by mass percentage: 35% to 45% graphene powder, 40% to 50% nano silver powder, 4% to 5% nickel powder, 5% to 6% nano palladium powder, and 5% to 6% nano copper powder. The graphene powder has a particle size of 10 nm, the nano silver powder has a particle size of 40 nm to 50 nm, the nickel powder has a particle size of 3 μm to 5 μm, the nano palladium powder has a particle size of 20 nm to 50 nm, and the nano copper powder has a particle size of 10 nm to 30 nm.

[0018] The role of adding small particles of graphene powder to the contact is to improve the contact's resistance to arc ablation. Graphite also has the ability to resist arc ablation, but the graphite particles are larger. At the same time, the wettability of graphite and silver is not as good as that of graphene and silver. Poor wettability leads to poor consistency of the formed silver-graphite contact material. The role of silver powder in the contact is to improve the conductivity and reduce the contact resistance of the contact. The role of nickel powder is to improve the corrosion resistance of the contact and make the contact more wear-resistant. This is because nickel has high hardness, silver is soft, and carbon is brittle. They are not wear-resistant and have a low service life, so a small amount of nickel is added. A small amount of nano-palladium powder mixed with silver powder can improve the corrosion resistance and wear resistance of the contact, slow down the discoloration of silver in the contact and the abnormal increase of contact resistance. This is because palladium itself is chemically inert and has a lower resistivity than silver. Adding copper powder to the contact can improve the corrosion resistance of the contact and increase the wear resistance of the contact. The conductivity of copper powder is second only to silver, which can ensure a low contact temperature rise of the contact and save a certain amount of silver.

[0019] The present invention also provides a method for preparing the silver-palladium-nickel-copper-graphene composite relay electrical contact, comprising the following steps: Step S01, mixing graphene powder with an organic solvent and deionized water to obtain a graphene solution. Specifically, since the graphene powder contains impurities and the particles are large, secondary preparation is required. Because graphene is hydrophobic, the graphene powder is added to the organic solvent ethanol. Since ethanol contains a small amount of water, a certain amount of deionized water needs to be added. The mass percentage is: 35%~40% graphene powder, 45%~50% ethanol, and 10%~15% deionized water are mixed in a clean container, and then stirred at a constant speed for 4h~5h with a stirrer. The stirred solution is placed in an ultrasonic cleaning pot and oscillated for 30 minutes to obtain a graphene solution.

[0020] Step S02, adding 80%-90% of the total amount of nano silver powder to the graphene solution, stirring to obtain a silver graphene solution. Specifically, adding 35%-40% of the nano silver powder to the graphene solution, placing it in a blender and stirring it for 2h-4h to obtain a silver graphene solution.

[0021] Step S03, the silver-graphene solution obtained in step S02 is sealed and allowed to stand for 12 to 14 hours, and the silver-graphene composite powder is placed in a ball mill for full stirring to obtain the silver-graphene composite powder. Specifically, the silver-graphene composite powder is filtered five times with a 300-mesh filter paper after the solution is sealed and allowed to stand for 3 to 4 hours, and the filtered solution is placed in a drying oven at 90° C. for 12 to 14 hours, and the silver-graphite composite powder is placed in a ball mill for full stirring to obtain the silver-graphene composite powder.

[0022] Step S04, add ethanol and deionized water to the remaining 10%-20% of nano silver powder, nickel powder, nano palladium powder, and nano copper powder, stir, oscillate, filter, obtain a mixed solution filtrate, dry the filtrate, and obtain a silver-nickel-palladium-copper mixed powder. Specifically, 5% to 10% of nano silver powder, 4% to 5% of nickel powder, 5% to 6% of nano palladium powder, and 5% to 10% of nano copper powder are placed in a clean container, and then 55% to 60% of ethanol and 10% to 15% of deionized water are poured into a blender and stirred for 2h to 4h to obtain a mixed solution, and then an ultrasonic cleaning pot is used for 1h to 2h oscillation, and the oscillated solution is filtered five times with 300 mesh filter paper, and the filtered mixed solution is placed in a drying oven at 90°C for drying for 12h to 14h to obtain a silver-nickel-palladium-copper mixed powder. The function of graphene powder is to improve the arc erosion resistance of the contact, and it has good wettability with silver; the function of silver powder is to improve the conductivity and reduce the contact resistance of the contact; the function of nickel powder, palladium powder and copper powder is to improve the corrosion resistance of the contact, make the contact more wear-resistant, and save a certain amount of silver.

[0023] Step S05, after the silver-graphene composite powder and the silver-nickel-palladium-copper mixed powder are stirred, the mixture is sealed and allowed to stand, and the mixed material after standing is hot isostatically pressed, sintered in a cavity containing hydrogen to form a material block; the material block is molded or wire-cut according to the required contact shape to obtain a molded contact. Specifically, the silver-graphene composite powder and the silver-nickel-palladium-copper mixed powder are placed in a ball mill for full stirring for 5h~6h, the ball milling speed is 5~10 times / second, and the mixture is sealed and placed for 3h~4h. The mixed material after placement is placed in an isostatic pressing device for hot isostatic pressing, the pressure is 200MPa~300MPa, and the pressure is maintained for 15min~20min. The long pressure holding time is to better remove the air gap inside the material, and the temperature is 950℃~1050℃ in a cavity containing hydrogen (purity above 95%) to form a material block. Hydrogen sintering is used to remove oxygen in the material. The material block is molded or wire-cut according to the required contact shape.

[0024] Step S06, decarburize the welding layer of the formed contact with a solvent, spray silver on the decarburized silver layer, and weld it to the contact piece. Specifically, the silver-graphene composite contact prepared by the above method improves the consistency, oxidation resistance, and arc ablation resistance of the contact, but the high proportion of graphene (proportion exceeding 10%) leads to poor weldability between the contact and the contact piece (the material is generally phosphor copper or magnesium copper) (because the graphene element is carbon, the weldability is poor, and welding pre-tinning cannot be performed). Figure 2 , 5 , 6. Therefore, the welding layer of the formed contact is further decarburized, and the decarburized silver layer is welded to the contact piece. Figure 1 , 3 As shown in 4, the concentration of the decarburizing solvent needs to be prepared in combination with the contact shape and the contact piece welding area. The contact welding area of ​​the present invention is 26.23mm 2 , under the condition of shear force ≥ 300N, the thickness of the decarburized layer needs to meet 50μm~80μm after testing. If it is lower than 50μm, the weldability is poor, and if it exceeds 80μm, the overall performance of the contact is reduced. According to the above parameters, the concentration of the decarburizer solution is proportioned. According to the mass percentage, 25%~30% of decarburizing powder, 60%~65% of ethanol, and 10%~15% of cyclopentane are put into a blender and stirred for 1h~2h. The role of ethanol is as a carrier to prepare the decarburizing solvent of the required concentration. Cyclopentane is to slow down the decarburizing solvent applied on the welding surface of the silver-graphite contact to further erode the carbon in the contact. After ball milling, pour the mixed solution into an ultrasonic cleaning pot for 1h of oscillation. The oscillated solution is filtered five times with 300-mesh filter paper. The filtered solution is used for decarburization of the contact welding layer. The decarburization solution is evenly sprayed on the surface of the welding layer. After 0.5h~1h, the contact welding layer is decarburized. Although silver is left, the disappearance of carbon leaves gaps. At this time, the welding layer needs to be sprayed with silver. The magnetron sputtering process is used for silver spraying. The silver spraying rate is 0.623nm / s, the sputtering power is 30W, the working gas pressure is 3.5Pa, and the silver spraying thickness is 50μm~80μm. The purpose of silver spraying is to fill the gaps left after decarburization as much as possible to improve the reliability of welding.

[0025] Example 1 35% graphene powder, 50% ethanol and 15% deionized water were stirred at a constant speed for 5 hours using a stirrer. The stirred solution was placed in an ultrasonic cleaning pot and oscillated for 30 minutes to obtain a graphene solution.

[0026] Add 40% of nano silver powder to the graphene solution, put it in a blender and stir it for 2 hours to obtain a silver graphene solution. After the solution is sealed and left to stand for 4 hours, filter the silver graphene solution five times with a 300-mesh filter paper, each filtering time is 1 hour, and place the filtered solution in a drying oven at 90°C for 12 hours to obtain a silver graphene composite powder. Put the silver graphite composite powder into a ball mill and stir it thoroughly.

[0027] 10% nano silver powder, 5% nickel powder, 5% nano palladium powder, and 5% nano copper powder are placed in a container, and 60% ethanol and 15% deionized water are poured in to mix. The mixed solution is poured into an ultrasonic cleaning pot for 1 hour of oscillation. The oscillated solution is sealed and placed for 2 hours. The solution after placement is filtered five times with 300 mesh filter paper, with an interval of 1 hour between each filtration. The filtered mixed solution is then placed in a drying oven at 90°C for 12 hours to obtain a silver-nickel-palladium-copper mixed powder. The silver-nickel-palladium-copper mixed powder is placed in a ball mill for full stirring.

[0028] 75% of silver-graphene composite powder and 25% of silver-nickel-palladium-copper mixed powder were put into a ball mill and stirred for 5 hours at a ball milling speed of 10 times / second. The mixture was sealed and placed for 4 hours. The mixed powder was placed in an isostatic pressing device for hot isostatic pressing at a pressure of 300MPa for 15 minutes to form a block. The block was sintered at a temperature of 950°C (range value) in a cavity containing hydrogen (purity above 95%) to form a block. The block was molded or wire-cut according to the required contact shape.

[0029] Put 25% decarburizing powder, 65% ethanol and 10% sulfolane into a mixer and stir for 2 hours. After standing for 1 hour, spray the solution evenly on the contact welding surface for decarburization. The contact is left for 1 hour. The decarburized layer is sprayed with silver by magnetron sputtering, and the thickness of the silver layer is 50μm.

[0030] Example 2 37% graphene powder, 53% ethanol and 10% deionized water were stirred at a constant speed for 5 hours using a stirrer. The stirred solution was placed in an ultrasonic cleaning pot and oscillated for 30 minutes to obtain a graphene solution.

[0031] Add 38% of nano silver powder to the graphene solution, put it in a blender and stir it for 2 hours to obtain a silver graphene solution. After the solution is sealed and left to stand for 4 hours, filter the silver graphene solution five times with a 300-mesh filter paper, each filtering time is 1 hour, and the filtered solution is placed in a drying oven at 90°C for 12 hours to obtain a silver graphene composite powder. Put the silver graphite composite powder into a ball mill and stir it thoroughly.

[0032] 10% nano silver powder, 5% nickel powder, 5% nano palladium powder, and 5% nano copper powder are placed in a container, and 60% ethanol and 15% deionized water are poured in to mix. The mixed solution is poured into an ultrasonic cleaning pot for 1 hour of oscillation. The oscillated solution is sealed and placed for 2 hours. The solution after placement is filtered five times with 300 mesh filter paper, with an interval of 1 hour between each filtration. The filtered mixed solution is then placed in a drying oven at 90°C for 12 hours to obtain a silver-nickel-palladium-copper mixed powder. The silver-nickel-palladium-copper mixed powder is placed in a ball mill for full stirring.

[0033] 75% of silver-graphene composite powder and 25% of silver-nickel-palladium-copper mixed powder were put into a ball mill and stirred for 5 hours at a ball milling speed of 10 times / second. The mixture was sealed and placed for 4 hours. The mixed powder was placed in an isostatic pressing device for hot isostatic pressing at a pressure of 300MPa for 15 minutes to form a block. The block was sintered at a temperature of 1050°C (range value) in a cavity containing hydrogen (purity above 95%) to form a block. The block was molded or wire-cut according to the required contact shape.

[0034] Put 25% decarburizing powder, 65% ethanol and 10% sulfolane into a mixer and stir for 2 hours. After standing for 1 hour, spray the solution evenly on the contact welding surface for decarburization. The contact is left for 1 hour. The decarburized layer is sprayed with silver by magnetron sputtering, and the thickness of the silver layer is 50μm.

[0035] Example 3 40% graphene powder, 50% ethanol and 10% deionized water were stirred at a constant speed for 5 hours using a stirrer. The stirred solution was placed in an ultrasonic cleaning pot and oscillated for 30 minutes to obtain a graphene solution.

[0036] Add 35% of nano silver powder to the graphene solution, put it in a blender and stir it for 2 hours to obtain a silver graphene solution. After the solution is sealed and left to stand for 2 hours, filter the silver graphene solution five times with a 300-mesh filter paper, each filtering time is 1 hour, and the filtered solution is placed in a drying oven at 90°C for 12 hours to obtain a silver graphene composite powder. Put the silver graphite composite powder into a ball mill and stir it thoroughly.

[0037] 10% nano silver powder, 5% nickel powder, 5% nano palladium powder, and 5% nano copper powder are placed in a container, and 60% ethanol and 15% deionized water are poured in to mix. The mixed solution is poured into an ultrasonic cleaning pot for 1 hour of oscillation. The oscillated solution is sealed and placed for 2 hours. The solution after placement is filtered five times with 300 mesh filter paper, with an interval of 1 hour between each filtration. The filtered mixed solution is then placed in a drying oven at 90°C for 12 hours to obtain a silver-nickel-palladium-copper mixed powder. The silver-nickel-palladium-copper mixed powder is placed in a ball mill for full stirring.

[0038] 75% of silver-graphene composite powder and 25% of silver-nickel-palladium-copper mixed powder were put into a ball mill and stirred for 5 hours at a ball milling speed of 10 times / second. The mixture was sealed and placed for 4 hours. The mixed powder was placed in an isostatic pressing device for hot isostatic pressing at a pressure of 300MPa and maintained for 20 minutes to form a block. The block was sintered at a temperature of 1050°C (range value) in a cavity containing hydrogen (purity above 95%) to form a block. The block was molded or wire-cut according to the required contact shape.

[0039] Put 25% decarburizing powder, 65% ethanol and 10% sulfolane into a mixer and stir for 2 hours. After standing for 1 hour, spray the solution evenly on the contact welding surface for decarburization. The contact is left for 1 hour. The decarburized layer is sprayed with silver by magnetron sputtering, and the thickness of the silver layer is 50μm.

[0040] Comparative Example 1 5% graphene powder, 70% ethanol and 25% deionized water were stirred at a constant speed for 5 hours using a stirrer. The stirred solution was placed in an ultrasonic cleaning pot and oscillated for 30 minutes to obtain a graphene solution.

[0041] Add 70% of nano silver powder to the graphene solution, put it in a blender and stir it for 2 hours to obtain a silver graphene solution. After the solution is sealed and left to stand for 2 hours, filter the silver graphene solution five times with a 300-mesh filter paper, each filtering time is 1 hour, and the filtered solution is placed in a drying oven at 90°C for 12 hours to obtain a silver graphene composite powder. Put the silver graphite composite powder into a ball mill and stir it thoroughly.

[0042] 10% of nano silver powder, 5% of nickel powder, 5% of nano palladium powder and 5% of nano copper powder were put into a container, and 60% of ethanol and 15% of deionized water were poured in to mix. The mixed solution was poured into an ultrasonic cleaning pot for 1 hour of oscillation. The oscillated solution was sealed and placed for 2 hours. The solution after placement was filtered three times with 300 mesh filter paper, with an interval of 1 hour between each filtration. The filtered mixed solution was then placed in a drying oven at 90°C for 12 hours to obtain a silver-nickel-palladium-copper mixed powder. The silver-nickel-palladium-copper mixed powder was placed in a ball mill for full stirring.

[0043] 75% of silver-graphene composite powder and 25% of silver-nickel-palladium-copper mixed powder were put into a ball mill and stirred for 5 hours at a ball milling speed of 10 times / second. The mixture was sealed and placed for 4 hours. The mixed powder was placed in an isostatic pressing device for hot isostatic pressing at a pressure of 300MPa for 15 minutes to form a block. The block was sintered at a temperature of 950°C (range value) in a cavity containing hydrogen (purity above 95%) to form a block. The block was molded or wire-cut according to the required contact shape.

[0044] In the comparative example, due to the low content of graphene, there is no need to decarburize the welding layer, and welding can be performed directly.

[0045] The electrical contact materials obtained in the embodiments of the present invention and the comparative examples were subjected to performance tests. At the same time, the electrical contact materials of Embodiment 1, Embodiment 2, Embodiment 3 and Comparative Example 1 of the present invention were subjected to electrical performance tests respectively. The test conditions were a DC resistive load of 220 V, 1 A, the contacts were energized and connected and disconnected 350 times, the operating frequency was 20 times / minute, and whether the contacts were welded was observed. The maximum arcing energy was recorded, and the results were shown in Table 1.

[0046] Table 1 is the performance test results of the electrical contact material of Example 1 .

[0047] As can be seen from Table 1, in Comparative Example 1, due to the relatively small proportion of graphene content, under the conditions of a DC resistive load of 220V and 1A, the contacts are welded and the arcing energy is relatively large (large arcing energy indicates that the contacts continue to arc, accelerating contact ablation). It can be seen from Example 1, Example 2, Example 3 and Comparative Example 1 that although the resistivity of the electrical contact material provided by the present invention is increased, the hardness of the contacts is increased, and the wear resistance of the contacts is enhanced. At the same time, the reduction in arcing energy helps to reduce the temperature rise of the contacts, reduce the probability of continuous arcing of the contacts, and reduce the risk of contact welding. A comparison of the arcing energy changes between Example 1 and Comparative Example 1 is shown in Figure 7 and Figure 8 .

[0048] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. Alterations, modifications, substitutions and variations of the above embodiments by a person skilled in the art are all within the scope of the present invention.

Claims

1. A silver-palladium-nickel-copper-graphene composite relay electrical contact, characterized in that: The ingredients are calculated by mass percentage: graphene powder 35%~45%, nano silver powder 40%~50%, nickel powder 4%~5%, nano palladium powder 5%~6%, and nano copper powder 5%~6%.

2. The silver-palladium-nickel-copper-graphene composite relay electrical contact according to claim 1, characterized in that: The graphene powder has a particle size of 10 nm, the nano silver powder has a particle size of 40 nm to 50 nm, the nickel powder has a particle size of 3 μm to 5 μm, the nano palladium powder has a particle size of 20 nm to 50 nm, and the nano copper powder has a particle size of 10 nm to 30 nm.

3. A method for preparing the silver-palladium-nickel-copper-graphene composite relay electrical contact according to any one of claims 1-2, characterized in that: The steps include: Step S01, mixing graphene powder, an organic solvent and deionized water to prepare a graphene solution; Step S02, adding 80%-90% of the total amount of nano silver powder into the graphene solution, and stirring to obtain a silver graphene solution; Step S03, sealing the silver-graphene solution obtained in step S02, leaving it to stand, filtering it, drying the filtrate, and stirring it in a ball mill to obtain a silver-graphene composite powder; Step S04, adding the remaining 10%-20% of nano silver powder, nickel powder, nano palladium powder, and nano copper powder into ethanol and deionized water, stirring, oscillating, filtering, obtaining a mixed solution filtrate, and drying the filtrate to obtain a silver-nickel-palladium-copper mixed powder; Step S05, after the silver-graphene composite powder and the silver-nickel-palladium-copper mixed powder are stirred, the mixture is sealed and allowed to stand, hot isostatic pressing is performed on the mixed material after the standing, and sintering is performed in a cavity containing hydrogen to form a material block; the material block is molded or wire-cut according to the required contact shape to obtain a molded contact; Step S06: Decarburize the welding layer of the formed contact with a solvent, spray silver on the decarburized silver layer, and then weld it to the contact piece.

4. The method for preparing the silver-palladium-nickel-copper-graphene composite relay electrical contact according to claim 3, characterized in that: In the step S01, graphene powder is added to ethanol and deionized water, and stirred at a constant speed for 4 h to 5 h using a stirrer. The stirred solution is placed in an ultrasonic cleaning pot and vibrated for 30 min to obtain a graphene solution.

5. The method for preparing the silver-palladium-nickel-copper-graphene composite relay electrical contact according to claim 3, characterized in that: In the step S02, the silver graphene solution is added to the graphene solution and placed in a mixer for thorough stirring for 2 h to 4 h to obtain a silver graphene solution.

6. The method for preparing the silver-palladium-nickel-copper-graphene composite relay electrical contact according to claim 3, characterized in that: In the step S03, the silver-graphene solution is sealed and allowed to stand for 3 h to 4 h, then filtered five times with 300-mesh filter paper, the filtrate is dried in a drying oven at 90° C. for 12 h to 14 h, and the dried silver-graphite composite powder is placed in a ball mill and fully stirred.

7. The method for preparing the silver-palladium-nickel-copper-graphene composite relay electrical contact according to claim 3, characterized in that: In the step S04, nano silver powder, nickel powder, nano palladium powder and nano copper powder are added to ethanol and deionized water, stirred in a stirrer for 2 h to 4 h, and then oscillated in an ultrasonic cleaning pot for 1 h to 2 h. The oscillated solution is filtered five times with 300 mesh filter paper, and the filtered mixed solution is placed in a drying oven at 90° C. and dried for 12 h to 14 h.

8. The method for preparing the silver-palladium-nickel-copper-graphene composite relay electrical contact according to claim 3, characterized in that: In the step S05, the silver-graphene composite powder and the silver-nickel-palladium-copper mixed powder are placed in a ball mill and stirred for 5h~6h, the ball milling speed is 5~10 times / second, and the mixture is sealed and allowed to stand for 3h~4h. The mixed material after standing is placed in an isostatic pressing device for hot isostatic pressing at a pressure of 200MPa~300MPa and maintained for 15min~20min; and sintered in a cavity containing hydrogen at a sintering temperature of 950℃~1050℃.

9. The method for preparing the silver-palladium-nickel-copper-graphene composite relay electrical contact according to claim 3, characterized in that: In the step S06, the decarbonization solvent is composed of 25% to 30% decarbonization powder, 60% to 65% ethanol, and 10% to 15% sulfolane.

10. The method for preparing the silver-palladium-nickel-copper-graphene composite relay electrical contact according to claim 3, characterized in that: In the step S06, the silver is sprayed by a magnetron sputtering process, the silver spraying rate is 0.623 nm / s, the sputtering power is 30 W, the working gas pressure is 3.5 Pa, and the silver spraying thickness is 50 μm to 80 μm.